Her Unexpected Match - Baker, Lacey (Shrewsbury, Pennsylvania : Amara, an imprint of Entangled Publishing, LLC, 2023)
Covering the human-interest story of an astrology-based matchmaker with a one hundred per cent success rate, cynical writer Allie Sparks, arriving in the quirky small town of Crescent Island, Maine, is sure shell debunk the mythical woman until an unexpected encounter makes her a believer.
Keywords: Women journalists -- Fiction; Dating services -- Fiction; Astrology -- Fiction; Man-woman relationships -- Fiction; Maine -- Fiction; Romance fiction; Novels